Life cycle assessment of poultry production in Nigeria: a review of sustainability and evaluation studies - Bawa, Hajara Salihu; Sharaai, Amir Hamza; Rahim, Rahima Ab; Sahrir, Syswani; Yuguda, Abubakar Umar (Italian Association of Chemical Engineering - AIDIC, 2023)
Poultry industry in Nigeria is one of the largest and fastest-growing sub-sectors of the agricultural sector, providing a significant source of income and protein to the country's population. However, there are concerns about the environmental and social impact of poultry production, and the need to evaluate its sustainability. The objective of this review article is to examine the sustainability and evaluation studies of the life cycle assessment (LCA) of poultry production in Nigeria. Literature review was employed in this study. The findings of this study indicate that the LCA approach is a valuable tool for evaluating the sustainability of poultry production in Nigeria. The findings revealed that poultry production in Nigeria has significant environmental impacts, primarily driven by methane emissions contributing to global warming potential. The industry also presents social and economic challenges, including concerns related to animal welfare, disease outbreaks resulting in economic losses, and inadequate support for farmers, emphasizing the importance of implementing sustainable practices and policy interventions. However, the review of existing literature indicates that there are still limitations in terms of data quality and methodological approaches within the research conducted on the subject matter. Therefore, this review recommends further research to address these limitations, and to develop more sustainable poultry production systems in Nigeria. Overall, this study highlights the need for a more holistic approach to evaluating the sustainability of poultry production, and the importance of promoting public awareness of the environmental and social impacts of this industry.